2016
DOI: 10.1002/esp.3890
|View full text |Cite
|
Sign up to set email alerts
|

Denudation intensity and control in the Chinese Tian Shan: new constraints from mass balance on catchment‐alluvial fan systems

Abstract: Tectonics and climate are usually seen as the main controlling factors of denudation rates, which seem to rise with the tectonic activity and to decrease when the climate becomes drier. However, the low denudation rates observed in semi-arid to arid contexts are generally measured on orogenic plateaus where the respective influence of the flat relief and the dry climate cannot really be unravelled. The Chinese Tian Shan was chosen as a case study. In the northern piedmont of this mountain range, a series of we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 114 publications
(313 reference statements)
0
38
0
Order By: Relevance
“…Guerit et al . () also suggested that the dry Central Asian climate of the last few million years is responsible for the imbalance between these very low erosion rates and the comparatively large shortening rates of 10 ± 3 mm year −1 (Reigber et al ., ).…”
Section: Geological Setting Of the North Piedmont Of The Eastern Tianmentioning
confidence: 97%
See 2 more Smart Citations
“…Guerit et al . () also suggested that the dry Central Asian climate of the last few million years is responsible for the imbalance between these very low erosion rates and the comparatively large shortening rates of 10 ± 3 mm year −1 (Reigber et al ., ).…”
Section: Geological Setting Of the North Piedmont Of The Eastern Tianmentioning
confidence: 97%
“…Guerit et al . () estimated erosion rates of around 0.135 mm year −1 for the last 300 kyr from the mass balance of 10 alluvial fans in the northern piedmont of the Eastern Tian Shan. Guerit et al .…”
Section: Geological Setting Of the North Piedmont Of The Eastern Tianmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this strong Pleistocene increase in slip rates suggests that a significant proportion (40-50%) of the recent deformation of the whole Tianshan is now accommodated across the Qiulitage and Yakeng anticlines only and that the deformation has migrated from inner structures toward the external structures of the piedmonts. This acceleration, also observed in northern Tianshan, may suggest evolution of the orogen center toward a more steady topography (Charreau et al, 2018;Guerit et al, 2016). We determined the vertical offset and its uncertainty by estimating the slopes and intercepts and associated uncertainties of the best-fit lines representing the surface on both side of the axial surface (Thompson et al, 2002).…”
Section: Accepted Articlementioning
confidence: 97%
“…Indeed, the geometrical reconstruction of a fan provides an estimate of its volume which, through mass balance, yields the average denudation rate of the catchment (Kiefer et al, 1997;Jayko, 2005;Jolivet et al, 2014;Guerit et al, 2016). Furthermore, when the river transports multiple grain sizes, it usually deposits the coarser sediment (gravel) near the fan apex and the finer sediment (sand) at its toe.…”
Section: Introductionmentioning
confidence: 99%